OBSERVATION ON THE INCIDENCE OF NON TYPHOID SALMONELLA (SEEOTYPEHAVANA), DRUG RESISTANCE AND PATHOGENIC STRENGTH TO THE CHILDREN OF less than ONE EYAR OLD AGE IRAN (1976-1986) - S. Mehrabian; B. Ghorishi A. Madjd (Tehran University of Medical Sciences, 1988)
A hundred and five strains of Salmonella havana were studied from the patients of pediatric hospital of Tehran and Tabriz during 1976-86. The sources of the strains in order to their frequency were from-stool, blood, spinal, fluid, wound and urine. From the epidemiological point of view Salmonella Havana is serotype of most non-typhoid Salmonella. All of the strains had drug resistancy and most of them were resistant to many drugs. Salmonella havana had been considered in the past as a serotype of nonpathogenic agent, but this work resulted that strain has Pathogenic strength to the children of under one year old age Symptoms of diseases caused by this strain were gastroenteritis, diarrhea, Vomiting fever, Focal infection, general infection and meningitis. This strain in about 20% of the cases, particularly in the children fewer than one year old age has caused death.